STRATEGIC PRIORITIES AND INVESTMENT DOMINANTS OF BUDGET POLICY DEVELOPMENT OF THE COUNTRY - KARPENKO, LIDIIA; VARESHCHENKO, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The research consists in substantiation and development of conceptual bases and recommendations on strategy of budgetary policy activization of Ukraine on the basis of investment. Investment analysis is a method of systematic analytical and research work to optimize investment decisions. Its indicators and methods of evaluation and interpretation are used in determining the effectiveness of alternative investment projects when it is necessary to make a choice. The main information and analytical tools for project evaluation: financial indicators of the project; indicators of economic efficiency; sensitivity analysis; break-even analysis; probability estimation. Their use is effective when using the discount method. Revision of the former regulatory system in accordance with the new priorities of economic policy provides assistance to the state in forming the infrastructure of the resource market, developing a network of non-bank financial institutions capable of mobilizing long-term financial resources, restructuring the banking system to implement investment functions of banks in the economy, insurance and investment incentives. The search for a new domestic model of investment development and the current mechanism of the state presence should be carried out taking into account the experience of state regulation of investment processes gained by foreign countries, using its positive aspects in Ukraine. state and administrative-territorial units. The purpose of the work is to study the systematization of the tool base for modelling the mechanism of budget management in the financial and economic system of the state and the development of conceptual approaches to the development of local budgets in the context of financial decentralization in Ukraine. Applied aspects are based on determining the main directions and effectiveness of budget policy in Ukraine for the period 2018-2020 pp. The authors study the structure of the budget mechanism and components of the budget management system as an instrumental basis for the conceptualization of local budgets in the economic system of the state. The practical part of the work is the monitoring of the investment sector of the Odessa region, the study of the dynamics of the main macroeconomic indicators of the region. In general, the implementation of administrative-territorial reform and the introduction of changes in the territorial organization of power in Ukraine have provided an update of the system of revenue generation of local budgets. The analysis of the selected research issues provides a conceptual basis for the formation of an effective mechanism of fiscal policy in Ukraine; forms a platform for developing macroeconomic stabilization policy. Prospects for further research are to improve the mechanism of effective functioning of the budget sphere and the implementation of integrated management analysis.